Understanding and investing in healthcare innovation and collaboration. Issue 4 (6th April 2020) - Day-Duro, Emma; Lubitsh, Guy; Smith, Gillian
Abstract : Purpose: To understand the partnership between clinicians and academics who come together to provide high-quality care alongside research and innovation, identifying challenges and productive conditions for innovation and collaboration across multi-disciplinary teams. Design/methodology/approach: An explorative action research methodology was adopted. Semi-structured interviews were conducted with 15 clinical, academic and executive leads at a large metropolitan tertiary care hospital with an academic health services portfolio in the UK. Findings: Clinical leaders recognise the division of limited resource, restrictive employment contracts and the divergent priorities of each organisation as challenges hindering the collaborative process and derailing innovation. Developing a culture of respect, valuing and investing in individuals and allowing time and space for interaction help facilitate successful innovation and collaboration. Successfully leading collaborative innovation requires a combination of kindness, conviction and empowerment, alongside the articulation of a vision and accountability. Research limitations/implications: Action research continues at this site, and further enquiry into the experiences, challenges and solutions of non-leaders when collaborating and innovating will be captured to present views across the organisation. Practical implications: Clinical and academic collaboration and innovation are essential to the continued success of healthcare. To ensure hospitals can continue to facilitate this in increasingly challenging circumstances, they must ensure longevity and stability of teams, devote time and resource to research and innovation, nurture interpersonal skills and develop kind and empowering leaders. Originality/value: This work uniquely focuses on a real-time collaborative and innovative development. By employing action research while this development was happening, we were able to access the real time views of those at the centre of that collaboration. We offer insight into the challenges and effective solutions that consultant-level clinical leaders encounter when attempting to innovate and collaborate in practice.